CONFLICT RESOLUTION BY INDIVIDUAL TRANSFORMATION - Akaninyene Umo, Udeme; Umofia, Inemesit Essiet (International Journal of Research -GRANTHAALAYAH, 2020)
There are many issues that most Nigerians have an agreement on. As a Contemporary Social Psychologist, one of these is that we want a better Nigeria. We need transformation in all our circumstances as a people and as a nation, to live in peace and unity for enduring economic development. This paper uses the theory of conflict by Karl Marx to interrogate how conflict resolution could be achieved through the process of individual transformation. All Nigerians are likely to agree that they want a peaceful, stable, and prosperous country. Nigerians as also aware of the reality of conflicts manifest in inter- communal clashes, ethnic rivalries, religious rivalries, and terrorism. While government often seek militarized approaches to conflict resolution, this paper, anchored on the belief that all conflicts are first personal before they become communal and national. The paper also proposes the deliberate education of the individual citizen on conflict resolution. The paper therefore examines types of conflicts, actors, conflict development in Nigeria and offers eighteen (18) conflict management approaches.